La eficiencia del gasto público en salud en América Latina en el periodo 2000-2017 - Paz Jiménez, Valeria Andreina (2021)
The Latin American and Caribbean region has increased public spending by seven percentage points in the last 20 years, but waste is equivalent to 4.4% of the production of the entire region. Therefore, the general objective of the research is to evaluate the efficiency of public spending on health in Latin America through frontier models in the period 2000-2017, for the development of the work statistical information available in secondary information sources was used: World Bank (2020), World Health Organization (2020) and Transparency International (2020). The methodology is based on an evolutionary and correlational analysis of the variables, also a Data Envelopment Analysis or DEA was used to measure the relative efficiency of the countries and finally a Tobit model was estimated. The results obtained show that there is an increasing trend of the variable public expenditure on health and a positive correlation with the variables life expectancy at birth, level of urbanization and corruption perception index, however, there is a negative correlation with the variables infant mortality rate and private expenditure on health, at the same time it is shown that only 20% of the units analyzed show relative efficiency throughout the period analyzed, it has also been identified that the level of urbanization, the percentage of private expenditure on health generate a negative effect, on the contrary, the corruption perception index shows a positive coefficient. The recommendations proposed are aimed at implementing policies aimed at strengthening institutions in the area of corruption, with the objective of not causing inefficiencies in them, and allowing better results to be achieved.